From 'populist moment' to authoritarian era: challenges, dangers, possibilities. Issue 7 (9th November 2020) - Edelman, Marc
ABSTRACT: This essay, inspired by the huge outpouring of research generated in and around the Emancipatory Rural Politics Initiative, reflects on the challenges of analysing authoritarian populism and particularly its rural expressions. The paper first examines key features of authoritarian populism and early populist movements in the Americas and Russia. Then it turns to 'illiberal' neoliberalism and the origins of neoliberalism under brutal dictatorial regimes in Indonesia and Chile. The paper scrutinizes the scepticism about populism in the work of prominent liberal and neoliberal media pundits and scholars. The affinities and tensions between different authoritarian populist rulers, the worrisome transnational linkages of their support bases and the massive flows of right-wing donor money between white supremacist and nationalist movements in different countries suggest the emergence of a fractious axis, not as consolidated as the fascist axis of the 1930s and 1940s, but a rising threat to democracy nonetheless. The paper considers the degeneration of progressive populisms, such as Venezuelan chavismo, and the problem of resorting to 'automatic' or 'unconditional' solidarities as a factor in the delegitimizing of left alternative voices. The last sections discuss emancipatory politics, the recent phenomenon of pandemic authoritarianism and the rising protest movements that constitute a possible opportunity for progressive forces.